Quasi-time-optimal steering law for low-thrust orbit transfer considering angular momentum and torque constraints - Kitamura, Kenji; Yamada, Katsuhiko; Shima, Takeya (Acta Astronautica, 2021)
In this study, a quasi-time-optimal steering law for low-thrust orbit transfer is investigated. In the proposed steering law, the satellite attitude is controlled to suppress its error with respect to the ideal thruster direction under the orthogonality constraint between the Sun direction and the solar array driving mechanism's rotational axis as well as the angular momentum and torque constraints. All these constraints are satisfied by introducing a structure similar to Baumgarte's stabilization method and by formulating a quadratically constrained quadratic programming problem which can be analytically solved to obtain the control torque. Several numerical simulations show that the transfer time difference from the ideal unconstrained transfer is less than a few percent. •A quasi-time-optimal steering law for low-thrust orbit transfer is derived.•Practical attitude constraints for low-thrust orbit raising are considered.•Control torque is derived by analytically solving a quadratic programming problem.•Transfer time difference from the ideal unconstrained case is only a few percent.